Properties of recycled polyethylene/chitosan composites: The effect of polyethylene-graft-maleic anhydride - Salmah, Huseinsyah; Azieyanti Nurain, Azmi (SAGE Publications, 2011)
Link to publisher's homepage at http://www.uk.sagepub.com/